Novel Mutation p.A64D in the Serpina 7 Gene as a Cause of Complete Thyroxine-Binding Globulin Deficiency Associated with Increases Affinity in Transthyretin by a Known p.A109T Mutation in the TTR Gene - Sklate, R. T. (2014)
Partial thyroxine-binding globulin deficiency (TBG-PD) is an endocrine defect with a prevalence of 1:4 000 in newborns. Due to the presence of a single TBG gene on the X chromosome, most familial TBG defects follow an X-linked inheritance pattern. Abnormal T4 binding to T4-binding prealbumin (TTR) is a rare cause of euthyroid hyperthyroxinemia, which is transmitted by autosomal dominant inheritance. The purpose of the present study was to identify and characterize new mutations in the Serpina7 and TTR genes in a complete family with typical TBG-PD. All patients underwent clinical and biochemical evaluation. Sequencing of DNA, population screening by (SSCP) analysis, and bioinformatics studies were performed. Molecular studies revealed a novel p.A64D mutation in the exon 1 of Serpina7 gene associated with the previously reported p.A109T mutation in the exon 4 of TTR gene. To our knowledge, this is the first report of a patient with a TBG-PD by a mutation in Serpina7 that was coincident with a mutation in TTR gene that increased affinity of TTR for T4. This work contributes to elucidate the molecular basis of the defects of thyroid hormone transport in serum and the improvement of the diagnosis avoiding unnecessary therapy.